Eksplorasi Program Bimbingan dan Konseling Terhadap Peningkatan Employability Skills Mahasiswa - Zakiah, Luna Nuranisa; Supriatna, Mamat; Yudha, Eka Sakti (Universitas Muhammadiyah Metro, 2023)
This study examines the career guidance program's effectiveness in developing the employability skills of Ariyanti Academy of Secretary and Management students. This study uses a positivism paradigm with reductionistic characteristics, oriented to causal relationships, logical, empirical, and deterministic based on a priori theory. The approach given in this study is a quantitative approach using quasi-experimental methods. This study compared the pretest scores and posttest scores of the experimental group and the control group. The main findings reveal that the Savickas theory-based career guidance program effectively develops the work skills of Ariyanti Academy of Secretary and Management students from cognitive, affective, and psychomotor aspects. This study provides suggestions for guidance and counseling practitioners to equip themselves with an understanding of student work skills.